Further Characterization of the Cellular DNA Hybridizing with the RNA of Rous Sarcoma Virus - Yoshikawa-Fukada, M. (1971)
Both 70S and 4S RNAs of Rous sarcoma virus (RSV) contain nucleotide sequences homologous to those in cellular DNA. Preparations of these RNAs were found to include some adventitious cellular sRNA. Nevertheless, both 70S and 4S RSV-RNAs were found by competition techniques to contain sequences distinct from those in cellular ribosomal RNA and 4S RNA. Competition experiments also reveal substantial homology between 70S and 4SRSV-RNA. In hybridization experiments performed in formamide at low temperatures, the melting profiles of hybrids between 70S RSV-RNA and cellular DNA, and 4S RSV-RNA and cellular DNA, are essentially superimposable. It is suggested that there are at least two origins of 4S RSV-RNA in RSV-RNA preparations: degradation of 70S RSV-RNA and inclusion of adventitious cellular 4S RNA. The possibility of a specific viral 4S RNA is not excluded.